2020
DOI: 10.1152/ajpcell.00053.2020
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling, DAMPs, and inflammation

Abstract: Danger sensing is one of the most fundamental evolutionary features enabling multicellular organisms to perceive potential threats, escape from risky situations, fight actual intruders, and repair damage. Several endogenous molecules are used to “signal damage,” currently referred to as “alarmins” or “damage-associated molecular patterns” (DAMPs), most being already present within all cells (preformed DAMPs), and thus ready to be released, and others neosynthesized following injury. Over recent years it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 33 publications
1
120
0
1
Order By: Relevance
“…The P2X7 receptor is a plasma membrane receptor gated by extracellular ATP, the earliest and most ubiquitous damage‐associated molecular pattern (DAMP) released at all inflammatory sites, the lungs included (Di Virgilio, Sarti, & Coutinho‐Silva, 2020; Tolle & Standiford, 2013). Very interestingly, increased ATP levels are also found in bronchoalveolar lavage fluid (BALF) from patients with ARDS or from mice with LPS‐induced acute lung injury (ALI) (Cicko et al, 2018).…”
Section: Figurementioning
confidence: 99%
“…The P2X7 receptor is a plasma membrane receptor gated by extracellular ATP, the earliest and most ubiquitous damage‐associated molecular pattern (DAMP) released at all inflammatory sites, the lungs included (Di Virgilio, Sarti, & Coutinho‐Silva, 2020; Tolle & Standiford, 2013). Very interestingly, increased ATP levels are also found in bronchoalveolar lavage fluid (BALF) from patients with ARDS or from mice with LPS‐induced acute lung injury (ALI) (Cicko et al, 2018).…”
Section: Figurementioning
confidence: 99%
“…77 CD39 hydrolyses ATP (adenosine triphosphate) which is released from damaged or apoptotic cells and acts as a DAMP. 78 Therefore, ATP's hydrolysis by CD39 acts as an immunosuppressive mechanism in healthy tissue. 77 Sato et al 77 67 CD4+ and CD8 + T cells are also increased within maternal blood surrounding the foetal villi, though they constitute a much smaller proportion of the infiltrate.…”
Section: Pathophys I Ology Of Chimentioning
confidence: 99%
“…the universal fundamental intermediate in biological energy transactions. Ample evidence shows that ATP is released via non-lytic mechanisms and accumulates into the extracellular space at sites of trauma or inflammation (Di Virgilio, Sarti, and Coutinho-Silva 2020). The P2X7R itself has a leading role in setting extracellular ATP levels since it has been shown that this receptor may serve as a conduit for ATP release (Pellegatti et al 2005) (Suadicani, Brosnan, and Scemes 2006).…”
Section: Discussionmentioning
confidence: 99%